The Influence of Confidence and Anxiety and Coordination Eyes on The Ability of The Penalty Kick on The Football Player Club Baruna Tumbak Mitra - Ahria Judistari Paturusi; Eduard Kumenap; Marnex W. Berhimpong; N. Piri; Achmad Paturusi (Sahabat Publikasi, 2026)
Here is the proofread and academically refined version with corrected grammar, improved methodological terminology, consistent tense, and proper sports science phrasing. The required phrase is italicized as requested:This research aimed to: (1) determine whether confidence had a direct effect on penalty kick ability; (2) determine whether anxiety had a direct effect on penalty kick ability; (3) determine whether eye-foot coordination had a direct effect on penalty kick ability; (4) determine whether self-confidence had a direct effect on anxiety; (5) determine whether self-confidence had a direct effect on eye-foot coordination; (6) determine whether anxiety had a direct effect on eye-foot coordination; and (7) examine the simultaneous influence of confidence, anxiety, and eye-foot coordination on penalty kick ability among football players of Club Baruna Tumbak Mitra. The study used a quantitative ex post facto research design. Path analysis was employed to examine the pattern of relationships among the independent variables and the dependent variable. The instruments used included a closed questionnaire to measure confidence and anxiety, the “Soccer Wall Volley Test” to assess eye-foot coordination, and a “Shooting Test” to measure penalty kick ability. Data were analyzed using univariate and bivariate statistical tests at an alpha level of 0.05. The results indicated that: (1) there was a significant effect of confidence on penalty kick ability, contributing 43.30%; (2) there was a significant effect of anxiety on penalty kick ability, contributing 40.96%; (3) there was a significant effect of eye-foot coordination on penalty kick ability, contributing 59.44%; (4) there was a significant effect of confidence on anxiety, contributing 65.77%; (5) there was a significant effect of confidence on eye-foot coordination, contributing 35.28%; (6) there was a significant effect of anxiety on eye-foot coordination, contributing 43.03%; and (7) there was a simultaneous significant influence of confidence, anxiety, and eye-foot coordination on penalty kick ability among football players of Club Baruna Tumbak Mitra, with a combined contribution of 66.59%.